Starting with Angular 5 - Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2018)
"Angular version 5 purpose: to keep this course on the cutting edge of Angular technology and be consistent in providing instruction for the features found in the latest Angular release (v5). In this update we addressed the major changes in the Angular version 5 major release. Per our course content, including hands-on coding exercises, there were a few breaking changes in the 5.1 releases which ripped across much of the original project code and also included minor, non-breaking changes which outdated certain aspects of our original content. We've updated all of the course's code-along video content with version 5 code, including: Angular-CLI repositioning & syntax usage related to its repositioning Angular-CLI & npm syntax usage Angular-CLI template output changes Material 2 Library Module massive positioning changes Material 2 inclusion and configuration syntax changes Material 2/Animations Module repositioning Fallout of the above deltas outdated a large percentage of the course's existing content. Each affected video in the series was updated to reflect the current release."--Resource description page.
Title from resource description page (Safari, viewed May 18, 2018).
Keywords: AngularJS (Software framework); Web site development; Web sites -- Design; Electronic books